UPAYA PENINGKATAN KESADARAN REMAJA TENTANG GIZI REMAJA UNTUK MENCEGAH ANEMIA REMAJA - Izah, Nilatul; Resty Himma Muliani; Fitriana Rakhimah; Sa’adah Handayani; Nina Maria Desi; Elqy Mei Zumaro (Politeknik Negeri Sriwijaya, 2023)
Adolescent development is as complex as that of children, because there are complex interactions between puberty, maturation, neurocognitive, and transitional social roles. In addition to the role of living conditions and the environment, especially at home, the key contributor to normal development is nutrition. It is necessary to consume healthy food, proper growth and development during puberty, which requires adequate macro and micro nutrients. Adjustment of energy and nutrient inputs, as well as the increasing variety of physical activities carried out by this age group. On the basis of these various factors, nutritional needs need to be prioritized because young women are prospective mothers who will give birth to the nation's next generation. The PKM activity was carried out with the aim of identifying adolescent nutrition as well as increasing adolescent knowledge about nutrition which was carried out at Bulakamba Vocational School, Brebes Regency on February 14, 2022, the number of participants who took part in PKM activities were 68 students. The results of PKM activities including Hb examination showed 50 students with normal status and 18 students with anemia status, 68 adolescents with normal nutritional status, 57 students, fat 5 students and thin students 6, there was an increase in knowledge from health education activities, from 23% (16 people) ) have good knowledge, 50% (34 people) have sufficient knowledge and 27% (18 people) have less knowledge to 56 people (83%) have good knowledge and 12 people (17%) have sufficient knowledge. Keywords: Adolescents, Youth Nutrition, Anemia